Internationalization strategies of companies in the wine industry in Portugal – context, forms of action and performance - Vivas, C. (2012)
This research work aims to analyze the competitive environment of companies in the wine sector and assess the implications in the development of strategic contingent guidelines and various performances. It proposes applying the methodological reference Integrated Grid for Strategic Reflection - IGSR (i), adapted to a context of international business IGSR(i), which structures research into two levels: a preliminary one, generic characterisation of the companies; along with a central one analysing its strategic strand, through the articulation of three components studied systematically (CRP) - contingent factors external and internal (C), the style of strategic reflection (R) and economic performance (P).